Hydrogen and Methane Production Under Conditions of Anaerobic Digestion of Key-Lime and Cabbage Wastes - Gaweł Sołowski; Izabela Konkol; Bartosz Hrycak; Dariusz Czylkowski (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
In this article, the results of key lime fruit (Citrus aurantifolia) wastes and cabbage (Brassica L.) wastes anaerobic digestion are presented. Anaerobic digestion of the wastes was performed in batch process, neutral pH (key-lime 7.47 and cabbage 7.67) and substrate concentration of Volatile Suspended Solids (VSS) 10 gVSS/L. One of the aims of this research was to check the availability of these substrates to be the source of methane and hydrogen. Key lime wastes produced 32 times more methane than raw cabbage. However, hydrogen production from cabbage was 149 times higher than key lime. The percentage of methane production in cabbage was up to 81% and in key lime was up to 75%. This research showed from the substrates comparison that efficient hydrogen production is less dependent on low pKa, pH than on total solids of the substrates.